1997
DOI: 10.1161/01.str.28.1.15
|View full text |Cite
|
Sign up to set email alerts
|

African Americans and Women Have the Highest Stroke Mortality in Texas

Abstract: Measures to prevent stroke mortality should emphasize its predilection for young AAs and women. A rigorous surveillance project is needed to determine whether stroke mortality is underestimated in the HA population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…5,7 Many investigations studied mortality from all types of stroke combined. Two of the 3 studies of sex difference in mortality caused by nonhemorrhagic stroke in the general population found increased risk among women, 6,8 whereas 2 of the 3 corresponding studies that measured case fatality rates among patients with acute stroke found increased risk among men. 4,5 There are many reasons for discrepancy between these studies with respect to the magnitude and the direction of sex difference in stroke mortality.…”
mentioning
confidence: 99%
“…5,7 Many investigations studied mortality from all types of stroke combined. Two of the 3 studies of sex difference in mortality caused by nonhemorrhagic stroke in the general population found increased risk among women, 6,8 whereas 2 of the 3 corresponding studies that measured case fatality rates among patients with acute stroke found increased risk among men. 4,5 There are many reasons for discrepancy between these studies with respect to the magnitude and the direction of sex difference in stroke mortality.…”
mentioning
confidence: 99%
“…6 Stroke mortality is higher in young MAs but reportedly lower in older MAs than in NHWs. 7,8 Risk factor profiles would predict higher stroke rates in MAs, 9 and indeed some have explained the lower stroke mortality in older MAs as a function of vital statistics error. 7,10 Intracerebral hemorrhage mortality is at least as high as that found in NHWs at all ages.…”
mentioning
confidence: 99%
“…7,12,25 These psychosocial and cultural differences may also foster a distrust of a NHW-run healthcare system, which may also explain both gender and race/ethnic differences. 4,18 Markedly increased delay times in hospital arrival and in evaluation by an emergency department physician was found in HA women presenting to the emergency room with acute stroke symptoms. 7 Similarly, these psychosocial norms may explain why women in New Mexico have a decreased knowledge of stroke risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,9 To prevent masking the interaction between age and ethnicity for stroke mortality, age adjustment was not used. 2,4 The stroke mortality rate for each race/ethnic group was calculated for the age-specific groups and by location. Rate ratios were calculated with NHW as the referent group, and 95% CIs were calculated by the Katz method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation